Protection of the fetus in the framework of genetic testing - Bouharara, Nesrine; Saidane, Asma (Journal of Human Sciences, 2022)
Genetic testing is a way to detect some genetic diseases that may be passed on to the fetus. The study of this topic aims to highlight the importance of this genetic examination before and after pregnancy, in protecting the fetus, through early diagnosis and treatment of genetic diseases. However, gene therapy is not comprehensive for all these diseases, given their abundance and it is not possible to detect all of them by genetic testing, but it is possible to protect the fetus from diseases that the parents carry and are aware of. The Algerian legislator also tried to keep pace with this medical development by legally regulating this medical technology.